2021
DOI: 10.3389/fcimb.2021.758392
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Inhaled Phage Therapy for Combatting Pulmonary Infections

Abstract: With respiratory infections accounting for significant morbidity and mortality, the issue of antibiotic resistance has added to the gravity of the situation. Treatment of pulmonary infections (bacterial pneumonia, cystic fibrosis-associated bacterial infections, tuberculosis) is more challenging with the involvement of multi-drug resistant bacterial strains, which act as etiological agents. Furthermore, with the dearth of new antibiotics available and old antibiotics losing efficacy, it is prudent to switch to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 212 publications
3
15
0
2
Order By: Relevance
“…Furthermore, we have observed that the use of lactoferrin prolonged the activity of bacteriophages on the biofilm and prevented its re-growth; this was observed after 24 h of incubation if phages were used alone. This corresponds with the reports of other researchers, which suggests that lactoferrin boosts and prolongs the effects of other antimicrobials [ 44 , 45 , 47 ]. Therefore, it can be assumed that the use of the phage–lactoferrin cocktail has potential application against biofilms formed by multi-drug-resistant bacteria, though the detailed mechanism remains to be determined [ 15 , 16 , 47 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, we have observed that the use of lactoferrin prolonged the activity of bacteriophages on the biofilm and prevented its re-growth; this was observed after 24 h of incubation if phages were used alone. This corresponds with the reports of other researchers, which suggests that lactoferrin boosts and prolongs the effects of other antimicrobials [ 44 , 45 , 47 ]. Therefore, it can be assumed that the use of the phage–lactoferrin cocktail has potential application against biofilms formed by multi-drug-resistant bacteria, though the detailed mechanism remains to be determined [ 15 , 16 , 47 ].…”
Section: Discussionsupporting
confidence: 92%
“…This corresponds with the reports of other researchers, which suggests that lactoferrin boosts and prolongs the effects of other antimicrobials [ 44 , 45 , 47 ]. Therefore, it can be assumed that the use of the phage–lactoferrin cocktail has potential application against biofilms formed by multi-drug-resistant bacteria, though the detailed mechanism remains to be determined [ 15 , 16 , 47 ]. We believe that more in vitro studies involving other phage types and bacterial genera, followed by in vivo studies, i.e., on Galleria mellonella or Caenorhabditis elegans models, could deliver more detailed data on phage–lactoferrin synergy and effectivity, helping to answer the question if phage–AMPs mixtures can be used as one of the treatment methods of multi-drug-resistant infections.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Dry powder formulations for phage inhalation have attracted increasing interests, partly because of the advantages of enhanced stability and shelf-life of phages in dry states [ 106 ]. SD, freeze drying and SFD are the commonly-used technique to prepare phage-based dry powders.…”
Section: Emerging Inhaled Antibacterials For Respiratory Bacterial In...mentioning
confidence: 99%
“…Regardless of the powder production technology, excipients play critical roles in stabilizing phages in the dry powder formulations upon production and storage. Amino acids, such as leucine and trileucine, are often used as dispersibility enhancers and moisture protectors, while sugars, including lactose, mannitol, trehalose and sucrose, are used as the stabilizers to preserve phages activities [ 106 ]. Table III summarizes the production methods and excipients used for phage powder production.…”
Section: Emerging Inhaled Antibacterials For Respiratory Bacterial In...mentioning
confidence: 99%